Elbow, forearm and wrist injuries in the athlete - Rettig, A. C. (Sports Medicine, 1998)
Competitive and recreational athletes sustain a wide variety of soft tissue, bone, ligament, tendon and nerve damage to their upper extremities. Most such injuries are related to direct trauma or repetitive stress, and account for a significant amount of 'down time' for athletes participating in a wide range of sports, particularly those in which the arm is utilised for throwing, catching or swinging. Overuse injuries to the elbow include musculotendinous injuries, ulnar nerve injuries and ligamentous injuries. Osteochondrol lesions of the capitellum and posterior impingement injuries in the joint are frequently seen in athletes as well. Acute traumatic injuries to the elbow include tendon ruptures, elbow dislocations and intra-articular fractures. Forearm overuse injuries in athletes include fracture of the carpal scaphold, fracture of the hook of the hamate, Kienbock's syndrome and pisoquetral syndromes. ligamentous injuries include scapholunate, lunotriquetral and midcarpal instability injuries. Injuries to the distal radio-ulnar joint and triangular fibrocartilage are also quite common in athletes, and require careful evaluation and treatment.